111k views
0 votes
Stuck in it 3 days ago, please some help. It's a literal equation question.

Stuck in it 3 days ago, please some help. It's a literal equation question.-example-1
User Inser
by
5.5k points

1 Answer

6 votes


d= √( (x_2 - x_1)^2 + (y_2 - y_1)^2 )


d^2= (x_2 - x_1)^2 + (y_2 - y_1)^2 }


d^2 - (x_2 - x_1)^2 = (y_2 - y_1)^2 }


|y_2 - y_1| = √( d^2 - (x_2 - x_1)^2)

Let's assume y₂ ≥ y₁. This is wrong; we shouldn't assume that; the question writers did this problem incorrectly. But we'll continue to get the answer they want you to choose.


y_2 - y_1 = √( d^2 - (x_2 - x_1)^2)


y_2 = y_1 + √( d^2 - (x_2 - x_1)^2)

Answer: A

The real answer is none-of-the-above. It's bad when the teachers who write these questions don't really know what they're doing.

The correct answer is y₂ is ambiguous:


y_2 = y_1 \pm √( d^2 - (x_2 - x_1)^2)

User Addaon
by
5.5k points